1997
DOI: 10.1016/s0895-7061(97)00061-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erythropoietin Administration on Blood Pressure and Urinary Albumin Excretion in Rats

Abstract: The effects of recombinant human erythropoietin (rHuEPO) administration on blood pressure and urinary albumin excretion were studied in normotensive Wistar-Kyoto rats (WKY), in spontaneously hypertensive rats (SHR), and in SHR rats treated with an angiotensin converting enzyme inhibitor (SHR-ACEi). Rats were housed in metabolic cages and treated with rHuEPO (150 U/kg body weight [bw] three times a week) for 6 weeks. Control animals received the vehicle only (0.25 mL of physiological saline). An angiotensin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been observed that treating chronic kidney disease (CKD) patients with EPO may lead to severe arterial HTN. This could be attributed to EPO-induced increased blood viscosity and decreased hypoxic vasodilatation [ 18 ]. Furthermore, it has also been noted that EPO increases calcium ion influx via opening L-type calcium channels in vascular smooth muscle cells and causes vasoconstriction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that treating chronic kidney disease (CKD) patients with EPO may lead to severe arterial HTN. This could be attributed to EPO-induced increased blood viscosity and decreased hypoxic vasodilatation [ 18 ]. Furthermore, it has also been noted that EPO increases calcium ion influx via opening L-type calcium channels in vascular smooth muscle cells and causes vasoconstriction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood volume was then calculated [21,22] as CBV (ml/100g) = [HbT]brain*MWHb*10 −4 / dt*[HbT]plasma*CLVHR, where [HbT]brain (mol/L) is the total hemoglobin concentration in brain tissue, MWHb = 64.5 kiloDalton molecular weight of hemoglobin, dt = 1.05 g/ml is the cerebral tissue density, [HbT]plasma (g/dl) is the hemoglobin concentration obtained from plasma and CLVHR = 0.69 is the cerebral to large vessel hematocrit ratio [23,24] (Further studies will be needed in order to understand the effect of age and hypertension on the cerebral-to-large vessel hematocrit ratio in order to improve the precision of CBV calculation). In the young animals, blood hemoglobin concentration was assumed to be 16 g/dL [22,[25][26][27].…”
Section: Nirs Data Analysismentioning
confidence: 99%